Targeted advertisement of chlamydia screening on social media: A mixed-methods analysis. (January 2019) - Nadarzynski, Tom; Burton, Jack; Henderson, Kimberley; Zimmerman, Deborah; Hill, Orla; Graham, Cynthia
Objective: Chlamydia is one of the most common sexually transmitted infections in teenagers and young adults. This study used a mixed-methods analysis to investigate targeted promotion of chlamydia home-testing on social media. Methods: Our first study, in which face-to-face interviews with young women were conducted, sought to explore their attitudes and preferences towards social media-based health promotion. Our second study used Facebook and Google analytics to examine visits to a chlamydia testing page (where chlamydia testing kits could be ordered online), both before and after a targeted Facebook-based health promotion campaign was conducted. Results: The interviews revealed Facebook to be the preferred choice of social media, with participants perceiving it to be a powerful and far-reaching platform for social interaction. Participants also highlighted several aspects of promotional content to be important at increasing engagement with the target population, including appropriate use of colour, level of interactivity, use of humour and anonymity. The website analysis showed a 277% increase in the direct entrance on the chlamydia testing kit page and a 41% increase in chlamydia test kit orders, in comparison with the baseline period prior to the intervention. Conclusions: The findings support social media as an engaging medium for the online promotion of chlamydia self-testing and implicate Facebook advertising as a useful tool in addition to community-based chlamydia screening services. Future research needs to identify whether targeted social media-based health promotion could lead to higher chlamydia diagnosis rate in comparison to traditional communication channels.